Penyuluhan Penggunaan Energi Listrik yang Efisien di Desa Banyumulek, Kediri, Lombok Barat - I Made Ari Nrartha; Sultan Sultan; I Made Ginarsa; Sudi Mariyanto Al Sasongko; Agung Budi Muljono (JURNAL KARYA PENGABDIAN, 2021)
Banyumulek village, Kediri sub-district is the center of the pottery industry in West Lombok Regency, NTB. Pottery is produced using traditional equipment and additional equipment that uses a power source for the production process. An understanding of how to use electrical equipment to reduce production costs and efficiency in consumption of electrical energy needs to be given to the public. The community service team of the Department of Electrical Engineering, University of Mataram provided counseling about this. The counseling was held at the Banyumulek village office which was attended by the village community and the Satria Rinjani youth group. The results of the evaluation based on the questionnaire analysis obtained that the majority were of productive age, i.e. 91.67% with an education level of 58.33% were high school and above, but all of them had never received counseling on the use of efficient electrical energy. The behavior of saving electricity is good, as much as 83.33%, even though they don't know how to use electricity efficiently.